Моtivation for Learning Science and Mathematics: Timss Research in Serbia - Nataša Z. Lalić-Vučetić; Snežana I. Mirkov (University of Belgrade, Teacher Education Faculty, 2023)
Student motivation is one of the affective components that plays a key role in learning science. Research shows that in developed countries there is a trend of declining students' interest in science and technology. In this paper, the relationships between intrinsic motivation, self-concept, and the achievement of the fourth-grade elementary school students in mathematics and sciences were investigated. The authors also present the results of the secondary data analyses obtained in Serbia by means of student questionnaires and knowledge tests in the last two cycles of the TIMSS research in 2015 and 2019. The questionnaire contains two scales in which motivational variables are operationalized: students' attitudes towards mathematics/sciences and mathematical/ scientific self-confidence. Students' attitude is an indicator of an intrinsic motivation, and self-confidence is an indicator of self-concept. The results show that students express a high motivation for learning mathematics and sciences and a high level of self-concept. A higher level of self-concept is accompanied by a higher level of motivation for learning mathematics and sciences. Individual characteristics of students have a greater influence on achievement than the influence of schools and teachers. Students who express a more positive attitude towards mathematics and science and a higher level of self-concept in these areas also have a higher level of achievement. The influence of mathematical self-concept on achievement is particularly significant. The obtained results are in accordance with the findings of the earlier research that indicate complex and controversial relationships between intrinsic motivation, self-concept, and mathematical achievement, as well as that other constructs, including self-concept, can mediate the links between motivation and achievement. The authors point out the possibilities of encouraging students' motivation for learning. If students are trained in the teaching process to organize their own activities, this will contribute to their experience of autonomy and the development of confidence in their own competence, which positively impacts their motivation for learning.